The role of company purpose and its internal communication in fostering organizational resilience in social enterprises - Kivinen, Matleena (My University, 2023)
Modern organizations have to navigate in an increasingly volatile operating environment, requiring resilience. Increased volatility, and the fact that some organizations handle disruptions better than others, has garnered the attention of researchers. Companies with a purpose, e.g., social enterprises, are said to handle disruptions better, because they serve fundamental needs, which stay relevant no matter what, and have committed employees. Thus, existing research has acknowledged the connection between company purpose and resilience, but it has yet to be looked into, which is what this study addresses. More specifically, how company purpose and its communication foster organizational resilience, is looked into. The research was carried out as a qualitative case study, examining a few cases in an intensive manner. In total, four semi-structured interviews were conducted between the end of January and mid-May of 2023, interviewing manager position employees in purpose-driven companies, i.e., social enterprises. The interviews were recorded and transcribed, ensuring no important details were missed. In addition, previous research, as well as secondary data in the form of case company web pages, were reviewed. The findings were then examined using a theoretical framework, which was established based on the literature review. The findings of this study back existing research to a great degree, stipulating that a connection does indeed exist between company purpose and resilience. When purpose is evident in company operations as well as communication, the result is committed employees and a company culture that is sensitive to change, enabling resilience. New findings based on this research highlight the role of employee wellbeing, as well as empowering, as commitment and resilience enhancing factors. Moreover, resilience is not only evident through awareness, adaptability, and the ability to recover, but through individual employees, who are capable of acting even in adverse circumstances. Finally, social enterprises inherently possess characteristics which make them resilient, such as increased awareness and adaptability, due to the services provided by them being largely dependent on the external environment. This study makes a theoretical contribution to discussions revolving around organizational resilience, purpose-driven organizations, e.g., social enterprises, and internal communication. Moreover, companies may find this study useful when examining their resilience and ways to enhance it.

Yritysten nykyinen toimintaympäristö on yhä enenevässä määrin epävakaa ja vaatii entistä enemmän resilienssiä. Lisääntynyt epävakaus sekä se, että jotkut organisaatiot selviytyvät toisia paremmin, ovat herättäneet tutkijoiden mielenkiinnon. Sanotaan, että yhteiskunnalliset yritykset pärjäävät paremmin epävakaassa ympäristössä, sillä ne vastaavat perustavanlaatuisiin tarpeisiin ja näiden yritysten työntekijät ovat usein sitoutuneempia. Tutkijat ovat siis tiedostaneet yhteiskunnallisten yritysten tarkoituksen ja resilienssin yhteyden, mutta asiaa ei ole tutkittu tarkemmin. Tässä tutkimuksessa tarkastellaan yrityksen tarkoituksen ja sen sisäisen viestinnän roolia yhteiskunnallisen yrityksen resilienssissä. Tutkimus toteutettiin laadullisena tapaustutkimuksena. Neljä puolistrukturoitua haastattelua toteutettiin tammi-toukokuun 2023 aikana, haastatellen yhteiskunnallisten yritysten johtotehtävissä olevia työntekijöitä. Haastattelut nauhoitettiin ja litteroitiin, jotta tärkeitä yksityiskohtia ei jäänyt huomaamatta. Primääridatan lisäksi tarkasteltiin aiempia tutkimuksia, sekä sekundääriaineistoa, kuten yritysten nettisivuja. Tutkimustuloksia tarkasteltiin hyödyntämällä teoreettista viitekehystä, joka muodostettiin kirjallisuuskatsauksen perusteella. Tutkimustulokset tukevat pitkälti olemassa olevaa tutkimusta ja väitettä, että yrityksen tarkoituksen ja resilienssin välillä on yhteys. Kun tarkoitus näkyy organisaation toiminnassa ja sisäisessä viestinnässä, on seurauksena sitoutuneet työntekijät ja muutosherkkä yrityskulttuuri, jotka edistävät resilienssiä. Tutkimustulokset korostavat uusina löydöksinä työntekijöiden hyvinvoinnin sekä voimaannuttamisen roolia työntekijöiden sitoutumista sekä yrityksen resilienssiä lisäävinä tekijöinä. Resilienssi ei ilmene pelkästään tietoisuuden, mukautuvuuden ja toipumiskyvyn kautta, vaan myös työntekijöiden kautta, jotka kykenevät toimimaan epäsuotuisissa olosuhteissa. Lisäksi yhteiskunnalliset yritykset ovat luonnostaan tietoisia toimintaympäristöstään, kuin myös sopeutuvaisia organisaatiorakenteiltaan, sillä palvelut, joita he tarjoavat, ovat riippuvaisia ulkoisesta ympäristöstä. Näin ollen yhteiskunnalliset yritykset omaavat luonnostaan resilienssiä edistäviä piirteitä. Tutkimuksen teoreettinen kontribuutio lisää keskustelua yhteiskunnallisista yrityksistä, organisaatioiden resilienssistä sekä sisäisestä viestinnästä. Lisäksi yritykset voivat hyödyntää tätä tutkimusta tarkastellessaan resilienssiään ja tapoja kehittää sitä.
Keywords: Organizational resilience, social entrepreneurship, social enterprise, purpose-driven organizations, internal communication